2016
DOI: 10.1097/aog.0000000000001204
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Clinical Trials Registries in Obstetrics and Gynecology Systematic Reviews

Abstract: A majority of systematic reviews in clinical obstetrics and gynecology journals do not conduct searches of clinical trials registries or do not make use of data obtained from these searches. Failure to make use of such data may lead to an inaccurate summary of available evidence and may contribute to an overrepresentation of published, statistically significant outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 11 publications
2
20
0
Order By: Relevance
“…Of the 137 viable articles identified in our analysis, we found that just 18 (13.1%) made use of CTRs. In comparison with findings in other fields of medicine, these findings were greater than those of anaesthesia (11.8%) and neurology (6.4%), but less than those of OB/GYN (18.4%) 21–23. In addition, it was found that despite the ever increasing number of clinical trials since the inception of the FDAAA in 2007, rising from 35 742 trials then to roughly 262 450 trials currently, researchers have consistently failed to make use of this vast amount of research in their data analysis 24.…”
Section: Discussionmentioning
confidence: 82%
“…Of the 137 viable articles identified in our analysis, we found that just 18 (13.1%) made use of CTRs. In comparison with findings in other fields of medicine, these findings were greater than those of anaesthesia (11.8%) and neurology (6.4%), but less than those of OB/GYN (18.4%) 21–23. In addition, it was found that despite the ever increasing number of clinical trials since the inception of the FDAAA in 2007, rising from 35 742 trials then to roughly 262 450 trials currently, researchers have consistently failed to make use of this vast amount of research in their data analysis 24.…”
Section: Discussionmentioning
confidence: 82%
“…The movement to standardize and improve the quality of systematic reviews and meta-analyses in the obstetric literature has gained momentum in the past decade, as evidenced by the growing collection of publications on the topic [ 46 50 ]. Although increased standardization of systematic reviews and meta-analyses in the medical literature [ 51 ] has been improved, one aspect—methods to limit publication bias—continues to lag behind [ 6 , 7 , 9 , 52 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analogous to current publications on the topic [ 6 , 8 , 9 ], we chose to limit our search to the 16 World Health Organization (WHO)-approved registries given the stringent requirements for clinical trial registration maintained by these registries. We also included ClinicalTrials.gov, as it appears to be the most frequently searched clinical trials registry [ 6 , 9 ]. The methods sections and any supplementary materials of each of the studies mentioning these clinical trials registries were carefully reviewed by Yerokhin and Carr to determine if the registry was searched, if usable data were found, and if the data were used for analysis in the publication.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic reviews were defined as studies that summarized research evidence from multiple studies and included information regarding inclusion and exclusion criteria, and search strategies. A meta-analysis was defined as a quantitative synthesis of primary study outcomes [4]. There were 293 systematic reviews and metaanalyses in our final sample, of which 292 were analyzed.…”
Section: Methodsmentioning
confidence: 99%